A method for determining the properties of multi-screen interfaces - Ngo, David Chek Ling; Teo, Lian Seng; Byrne, John G. (Zielona Góra: Uniwersytet Zielonogórski)
An important aspect of screen design is aesthetic evaluation of screen layouts. While it is conceivable to define a set of variables that characterize the key attributes of many alphanumeric display formats, such a task seems difficult for graphic displays because of their much greater complexity.
Keywords: screen design; interface aesthetics; aesthetic measures; aesthetic characteristics; multi-screen interfaces